Gambaran Karakteristik Ibu Bersalin dengan Sectio Cesarea di RSUD Sungai Lilin Kabupaten Musi Banyuasin: Description of the Characteristics of Maternity with Sectio Cesarea at Sungai Lilin Hospital, Musi Banyuasin Regency - Hestin Dwi Rahayu; ariA Widyaningsih (Journal of Holistics and Health Sciences (JHHS), 2022)
According to WHO (World Health Organization) the average standard of sectio cesarean (SC) operation is around 5 - 15%. Data from the WHO Global Survey on Maternal and Perinatal Health showed that 46.1% of all births were by cesarean delivery. The number of maternal deaths in South Sumatra Province in 2018 was 120 people, an increase from 2017. Even at Sungai Lilin Hospital there were the most cases that were a threat, namely in Sectio Cesarean (SC) deliveries, namely in 2018 as many as 83 (18.9%) people. , in 2019 as many as 93 (21.2%) people, in 2020 as many as 97 (22.1%) people and in 2021 (January-November) as many as 166 (37.8%) people, which has increased from 2018-2021 . To describe the characteristics of mothers giving birth with cesarean section at Sungai Lilin Hospital, Musi Banyuasin Regency in 2021. This study used a descriptive analytic survey method with a cross sectional approach. The population of this study were all mothers who gave birth at Sungai Lilin Hospital in 2021 (January-November) with a total sample of 166 respondents. Shows that there are 103 respondents (62.0%) who perform cesarean section in low education, compared to 63 respondents (38.0%) with higher education. At the age of the mother, it is more common at the age of the mother who is not at risk (>20-< 35 years) as many as 124 respondents (74.7%) of the mothers with risk age (<20->35 years) as many as 42 respondents (25.3%) and in parity mothers who gave birth a lot by cesarean section, parity multiparous mothers were 101 respondents (60.8 %), the parity of primiparous mothers was 51 respondents (30.7%) and the parity of grandemultiparous mothers was 14 respondents (8.4%). The conclusion of the research shows that the incidence of cesarean section based on education is more in low education as many as 103 respondents (62.0%), at age it is more common at the age of mothers who are not at risk (>20-<35 years) as many as 124 respondents (74.7%) and on parity multiparous mothers as many as 101 respondents (60.8%). It is hoped that it can be input and strive for the patient's mindset about not distinguishing between education and medical indications. ABSTRAK Menurut WHO (World Health Organization ) standar rata-rata operasi sectio cesarea (SC) sekitar 5 - 15%. Data WHO Global Survey on Maternal and Perinatal Health menunjukkan 46,1% dari seluruh kelahiran melalui persalinan SC. Jumlah kematian ibu maternal di Provinsi Sumatera Selatan tahun 2018 sebanyak 120 orang meningkat dari tahun 2017. Bahkan di RSUD Sungai Lilin terdapat kasus terbanyak yang menjadi ancaman yaitu pada persalinan sectio Cesarea (SC) yaitu pada tahun 2018 sebanyak 83 (18,9%) orang, tahun 2019 sebanyak 93 (21,2%) orang ,tahun 2020. Sebanyak 97 (22,1%) orang dan tahun 2021 (Januari-November) sebanyak 166 (37,8%) orang, yang mengalami peningkatan dari tahun 2018-2021. Untuk mengetahui gambaran karakteristik ibu bersalin dengan sectio cesarea di RSUD Sungai Lilin, Kabupaten Musi Banyuasin tahun 2021. Penelitian ini menggunakan penelitian deskriptif metode survei analitik dengan pendekatan cross sectional. Populasi penelitian ini adalah seluruh ibu yang melahirkan di RSUD Sungai Lilin tahun 2021 (Januari-November) dengan sampel yang diambil secara total sampling berjumlah sebanyak 166 responden. Distribusi frekuensi pada pendidikan rendah sebanyak (62.0%) dari pada ibu yang pendidikan tinggi sebanyak (38.0%) , pada umur ibu lebih banyak terjadi pada usia ibu tidak beresiko (>20-<35 tahun) sebanyak (74.7%) dari pada ibu dengan usia berisiko (<20->35 tahun) sebanyak (25.3%) dan pada paritas ibu yang banyak melahirkan dengan sectio cesarea paritas ibu multipara sebanyak (60.8%), paritas ibu primipara sebanyak (30.7%) dan paritas ibu grandemultipara sebanyak (8.4%). kesimpulan hasil penelitian menunjukkan bahwa kejadian tindakan sectio cesarea berdasarkan pendidikan lebih banyak pada pendidikan rendah sebanyak (62.0%), pada umur lebih banyak terjadi pada usia ibu tidak beresiko (>20-<35 tahun) sebanyak (74.7%) dan pada paritas ibu multipara sebanyak (60.8%). Diharapkan agar dapat bisa menjadi masukan dan mengupayakan terhadap pola pikir pasien tentang tidak membedakan antara pendidikan dengan indikasi medis.